The SCL transcriptional network and BMP signaling pathway interact to regulate RUNX1 activity. - Pimanda, J; Donaldson, I; de Bruijn, M; Kinston, S; Knezevic, K; Huckle, L; Piltz, S; Landry, JR; Green, A; Tannahill, D; Göttgens, B (2007)
Hematopoietic stem cell (HSC) development is regulated by several signaling pathways and a number of key transcription factors, which include Scl/Tal1, Runx1, and members of the Smad family. However, it remains unclear how these various determinants interact. Using a genome-wide computational screen based on the well characterized Scl +19 HSC enhancer, we have identified a related Smad6 enhancer that also targets expression to blood and endothelial cells in transgenic mice. Smad6, Bmp4, and Runx1 transcripts are concentrated along the ventral aspect of the E10.5 dorsal aorta in the aorta-gonad-mesonephros region from which HSCs originate. Moreover, Smad6, an inhibitor of Bmp4 signaling, binds and inhibits Runx1 activity, whereas Smad1, a positive mediator of Bmp4 signaling, transactivates the Runx1 promoter. Taken together, our results integrate three key determinants of HSC development; the Scl transcriptional network, Runx1 activity, and the Bmp4/Smad signaling pathway.